DIGITAL PRESERVATION AND INTELLIGENT INNOVATION IN TRADITIONAL AND MODERN ARTS - Verma, Dr. Amit; Kale, Archana; Agarwal, Krati; Chandratreya, Abhijit; Rani, Archana; Ajani, Samir N. (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This special issue of ShodhKosh: Journal of Performing and Visual Arts explores how digital preservation and intelligent innovation are transforming traditional and modern arts. It highlights AI-driven archiving, restoration, and revival of cultural heritage alongside generative design, computational aesthetics, and human–AI co-creation in contemporary practice. The issue also examines AI-enhanced arts education through adaptive learning, predictive analytics, and inclusive pedagogy. Additionally, it addresses intelligent museum systems, blockchain provenance, and data-driven cultural management. By engaging ethical and philosophical debates on authorship and creativity, the collection emphasizes responsible integration of technology to sustain heritage while fostering innovation in the digital age. Issue Editor: Dr. Amit Verma Associate Professor and Assistant Registrar in Journalism & Mass Communication, Centre for Distance and Online Education (CDOE), Manipal University Jaipur, Rajasthan, India Email: amit.verma@jaipur.manipal.edu / amitve4@gmail.com Dr. Archana Kale Associate Professor, Computer Engineering, MES Wadia College of Engineering, Pune, India Email: archana.kale@mescoepune.org Dr. Krati Agarwal Noida International University, Noida, India Email: drkratiagarwal0820@gmail.com Abhijit Chandratreya Associate Dean (PhD Programs), Indira University, Pune, India Email: abhijit.indira@gmail.com Dr. Archana Rani Head and Associate Professor, Department of Fine Arts, R G College, Meerut, India Email: rgpgcollegemrt@gmail.com / drarchana.art@gmail.com Dr. Samir N. Ajani School of Computer Science and Engineering, Ramdeobaba University (RBU), Nagpur, India Email: samir.ajani@gmail.com